2003
DOI: 10.1134/1.1663998
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the absorption length of inclined extensive air showers

Abstract: The dependence of the number of extensive air showers (EAS) on the zenith angle ϑ is obtained in groups with a constant solid-angle step with different selection types at separations between stations of 500 and 1000 m by using the Yakutsk EAS array data. A bend point is formed at the zenith angle ∼50°. This point shifts with the increasing energy in the direction corresponding to the shift of the cascade-curve maximum depth with the variation of energy. The boundaries of change of these dependences obtained se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…There exist some other observations which could favour this interpretation. First, there is a strong excess [40,41] of showers with energies above 10 18 eV at large zenith angles (> 60 o ). Second, experiments at Pierre Auger Observatory Surface Array revealed that "a significant number of very horizontal events are detected, offering a novel view of EAS" [42].…”
Section: Discussionmentioning
confidence: 99%
“…There exist some other observations which could favour this interpretation. First, there is a strong excess [40,41] of showers with energies above 10 18 eV at large zenith angles (> 60 o ). Second, experiments at Pierre Auger Observatory Surface Array revealed that "a significant number of very horizontal events are detected, offering a novel view of EAS" [42].…”
Section: Discussionmentioning
confidence: 99%
“…In [1] the presence of bent point depending on the number of extensive air showers (EAS) with E 0 >10 18 eV on a zenith angle ϑ is shown. At first, as a zenith angle ϑ increases, the number of showers decreases or remains constant and then after reaching ∼50° a considerable rise of them begins.…”
mentioning
confidence: 99%
“…Showers have been divided into groups with a constant step in cosϑ which corresponds to a constant solid angle [1]. The charged particle absorption length at a distance of 600 m from the axis λ 600 and the energy have been calculated by formulae accepted at the Yakutsk array [2,3].…”
mentioning
confidence: 99%